Peran Fraud Triangle dalam Mendeteksi Financial Statement Fraud di Perusahaan Perbankan ASEAN - Yuwono, Yuliana Pertiwi; Marlina, Maria Assumpta Evi (E-Jurnal Akuntansi; Vol 31 No 3 (2021), 2021)
This research aims to determine the effect of fraud triangle theory toward Financial statement fraud. Financial statement fraud is proxied by earnings management.  Population in this study is non-Islamic commercial banking companies listed on SGX, MYX, SET, PSE and IDX. The sampling technique used purposive sampling. The total sample in the study was 66 non-Islamic commercial banking companies. The data analysis method used is multiple linear regression. The research results proved that Financial targets and change of auditors had a positive effect on Financial statement fraud while external pressure had a negative effect on Financial statement fraud. Financial stability and ineffective monitoring had no effect on Financial statement fraud. This research can be used as a reference by investors, the public, government and users of other financial statement information in order to detect Financial statement fraud through the fraud triangle theory. Keywords: Financial statement fraud; Earnings Management; Fraud Triangle.